Pengaruh Air Mengunakan Reclaimed Asphalt Pavement Pada Campuran Beton Aspal Berdasarkan Uji Cantabro Dan Indirect Tensile Strength - Tommy Iduwin; Devita Mayasari; Tri Yuhanah (FORUM MEKANIKA, 2021)
The impact of RAP on water was identified to be analyzed for the material's resistance to water because there are still a lot of waterlogged pavements in Indonesia. This research uses RAP variation 0%, 25% and 35%. The test is the Marshall test to get the optimum asphalt content value, the Cantabro test to determine the weight loss for 300 rounds and the durability by varying the immersion 0.1, 2, 4 and 7 days which will be tested for ITS. The KAO value obtained for each variation is 5.4% for 0% Rap, 5.6 for 25% Rap and 6% for 35% RAP. The results of the Cantabro test show that the largest percentage of weight loss is a mixture of 35% RAP which is 12.54%, where for 0% RAP there is a weight loss of 10.85% and at 25% RAP there is a weight loss of 11.66%. ITS test results have the highest value with variations of RAP 0%, RAP 25% and RAP 35%. variations of 0%, 25% and 35% showed a decreasing trend until the 7th day of immersion, it can be said that in the three variations the ITS value was influenced by the duration of continuous immersion. Keywords: RAP, AC-WC, Marshall, Cantabro, Indirect Tensile Strength